ANALISIS KETERAMPILAN BERBICARA DAN MENULIS BAHASA INGGRIS MAHASISWA MELALUI METODE TEBAK GAMBAR - Febriani Hastini Nasution; Nurhidaya Fithriyah Nasution (Institut Pendidikan Tapanuli Selatan, 2019)
The purpose of this research was to analyze the college students’ English speaking and writing skill through Picture-Guessing method in Advanced English for Physics subject. The research method was quantitative descriptive research. The population was the entire of college students in fourth semester of Physics Education Study Program which amount of student was six people. All population in this research became a sample of this research. The technique of sampling was total sampling. The treatment was conducted was applying the Picture-Guessing method. The result of research were: 1) The average value of college students’ English speaking skill was 70.73 in “Good” category; 2) The average value of college students’ English writing skill was 72.83 in “Good” category.